Struktur Populasi Buta-Buta (Excoecaria Agallocha L.) Di Kawasan Mangrove Desa Tabanio Kabupaten Tanah Laut - Noorhasanah .; Mahrudin . (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
Plant population structure includes density, distribution, age classification, and conservation status. This study analyzes the population structure of Excoecaria agallocha L. (buta-buta) in the mangrove area of Tabanio Village, South Kalimantan, based on age classification by Odum (1993) and rarity status by IUCN (2014). The survey was conducted from September 2024 to June 2025 using 10 × 10 m quadrats and descriptive analysis. Results show a stable population with densities of 607 individuals/ha (pre-reproductive), 433 individuals/ha (reproductive), and 187 individuals/ha (post-reproductive). The age structure forms a broad-based pyramid, dominated by young individuals, indicating good natural regeneration. According to the IUCN, the species is classified as Least Concern, suggesting it is not at immediate risk of extinction. Nevertheless, ongoing protection and sustainable mangrove habitat management are essential to maintain population stability. This study contributes to mangrove ecological understanding and supports more sustainable conservation strategies in South Kalimantan.